Desenvolvimento de um programa e avaliação de material autoinstrucional para formação de agentes favorecedores de comportamento de estudo - Coser, Danila Secolim (2013)
The engagement of parents, and adults in general, with the academic activities of children is an important factor for establishing adequate study conditions as early as possible, avoiding that this kind of learning happens by chance, through trial and error and coercive control. Based on the behavior analysis theory and the teaching technology denominated educational programming , the current work aims to develop and evaluate an individualized material for training adults for being agents that favor the studying behavior of children. The research was divided in two phases: 1. Elaboration of teaching material, based on teaching programming procedures and knowledge gathering already available. 2. Evaluation of the material regarding its efficiency as a condition for training agents for favoring the studying behavior. At the first step the following activities were done: a. description of the problem in which intervenes through the teaching programming; b. proposal of terminal teaching objectives, which could solve the problem, in a behavior form.; c. decomposition of the terminal objectives proposed in all the necessary actions to achieve them; d. identification of the working parts and intermediary objectives; e. definition of the starting repertoire of the apprentices in a behavior manner; f. teaching objectives sequencing according to complexity levels; g. teaching and evaluation planning; h. instructions, information, texts redacting for six modules of the teaching programming. The first phase results highlights the teaching programming potential, given that, compared to other subjects of the area, the defined teaching objectives seem more complete. During the second phase of the research, five participants used different parts of the individualized teaching material for training adults for being favoring behavioral studying agents; the same participants answered an evaluation form before, during and after the exposition to the teaching programming. The retrieved data allows affirming that the teaching programming material developed in this study is adequate as self-teaching material, with personalizes rhythm and composition, with an specific selection and sequencing of teaching units to be met. The systematic evaluation of the apprentices performance during the program activities shows some aspects of the programming teaching conditions that need to be reviewed. However, the verification of the training effects was impaired by the fact that the material was applied only partially for each participant and in a period near the children school holyday, preventing the conclusion of the practical activities. Finally, it is discussed aspects that should be considerate for future researches in this topic, such as: full teaching application programming; application period for the apprentices; development of all modules foreseen in teaching programming; review of the teaching conditions regarding the applied resources, amongst others.